2008
DOI: 10.1016/j.neuropsychologia.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Specific impairments in the recognition of emotional facial expressions in Parkinson's disease

Abstract: Studies investigating the ability to recognize emotional facial expressions in non-demented individuals with Parkinson's disease (PD) have yielded equivocal findings. A possible reason for this variability may lie in the confounding of emotion recognition with cognitive task requirements, a confound arising from the lack of a control condition using non-emotional stimuli. The present study examined emotional facial expression recognition abilities in 20 non-demented patients with PD and 23 control participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(186 citation statements)
references
References 92 publications
12
166
2
6
Order By: Relevance
“…Thy1-aSyn mice show an agedependent deficit in this task, as well as in fear conditioning, likely to be due to the expression of a-synuclein aggregates in the amygdala (Freichel et al 2007), a brain area known to mediate emotional processes. These data are in line with the presence of Lewy bodies and Lewy neurite deposits in the amygdala of PD patients (Braak et al 1994), as well as the selective impairment in the recognition of facial emotion (Clark et al 2008) and blunted reactivity during aversive/unpleasant events observed in these patients (Bowers et al 2006).…”
Section: -Ohda-and Mptp-based Rodent Modelssupporting
confidence: 83%
“…Thy1-aSyn mice show an agedependent deficit in this task, as well as in fear conditioning, likely to be due to the expression of a-synuclein aggregates in the amygdala (Freichel et al 2007), a brain area known to mediate emotional processes. These data are in line with the presence of Lewy bodies and Lewy neurite deposits in the amygdala of PD patients (Braak et al 1994), as well as the selective impairment in the recognition of facial emotion (Clark et al 2008) and blunted reactivity during aversive/unpleasant events observed in these patients (Bowers et al 2006).…”
Section: -Ohda-and Mptp-based Rodent Modelssupporting
confidence: 83%
“…This is congruent with the meta‐analysis by Gray and Tickle‐Degnen 12. Two years earlier, Clark and collaborators13 also underlined the deleterious impact of this deficit on patients' social relationships, highlighting a negative correlation between their FER difficulties and their level of interpersonal distress.…”
Section: Facial Emotion Recognition In Pdsupporting
confidence: 77%
“…Concomitant with depression, apathy and anxiety are also frequent in PD 3, 99. However, these mood disorders have been taken into account less often, although some studies have highlighted their influence on FER (anxiety: Clark et al13 and Ille et al33; apathy: Robert et al100 and Martínez‐Coral et al25). …”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…Evidence indicates the individuals with PD have deficits in recognizing emotions from prosody (Dara et al, 2008;Pell and Leonard, 2003;Yip et al, 2003) and facial expressions (Ariatti et al, 2008;Clark et al, 2008;Dujardin et al, 2004), although not all findings have been consistent. Several studies have failed to find impaired performance in the recognition of facial expressions related to emotion in their PD samples (Adolphs et al, 1998;Pell and Leonard, 2005), whereas others have failed to find deficits in recognition from prosody (Clark et al, 2008;Kan et al, 2002). In a recent meta-analysis of the literature comparing emotional recognition abilities of individuals with PD and healthy controls (HC), Grey and Tickle-Degnen concluded that there is a robust link between PD and deficits in emotion recognition using both voice and faces, with impairments particularly marked with respect to negative emotions (Gray and Tickle-Degnen, 2010).…”
Section: Introductionmentioning
confidence: 99%